Implementation of Inquiry based Learning with OE3R Strategy and the Impacts to Students' Conceptual Understanding in Fundamental of Analytical Chemistry - Rahmadhani, Pradita; Sutrisno, Sutrisno; Widarti, Hayuni Retno (Jurnal Ilmu Pendidikan, 2020)
Chemistry created based on process how scientists work and think to understanding a phenomenon or problem that occurs in natural world. That activities gained through physical and mental activities. Discoveries on Science are obtained and solved using inquiry thinking. Many inquiry-based learning strategies have been developed, one of it’s the OE3R (Orientation – Exploration – Explanation – Elaboration - Reflection) Strategy.  The purpose of implementation of OE3R strategy on lecturing Fundamental of Analytical Chemistry are to determine effectiveness and differences of students’ conceptual understanding achievements. This research design using a Quasy experiment with pretest and posttest in two groups with different treatment. The Experimental Group learn using OE3R strategy, then the Control Group using conventional strategy based lecturer method. The subject of research was student in Fundamental of Analytical Chemsitry courses at Chemistry Department, Universitas Negeri Malang. The result show that inquiry-based learning with OE3R strategy as innovation learning effective to make differences of students’ conceptual understanding achievements in this courses.